The Elusive Role of the Left Temporal Pole (BA38) in Language: A Preliminary Meta-Analytic Connectivity Study. (21st October 2014) - Ardila, Alfredo; Bernal, Byron; Rosselli, Monica
Abstract : It has been suggested that the left temporal pole (Brodmann area 38 (BA38)) participates in diverse language functions, including semantic processing, speech comprehension, and naming. Utilizing the activation likelihood estimation (ALE), a meta-analytic connectivity study was conducted to further our understanding on the role of BA38 in language. Departing from the BrainMap functional database, 11 papers corresponding to 12 paradigms including 201 participants were selected. Initially, P < 0.01 was employed as the significance level, resulting in the presence of four different activation clusters. However, when the significance level was lowered toP < 0.05, sixteen activation clusters appeared, including classical language areas such as Broca's and Wernicke's areas. It was concluded that (1) this meta-analytic connectivity study suggests the presence of two major connection circuits involving BA38; one is related to language, while the other may be involved in visuospatial and integrative audiovisual functions. Furthermore, (2) BA38 also contributes to various brain networks supporting linguistic processes related not only to language comprehension but also to language production.